Morphology and anatomy of inflorescence and inflorescence axis in Paepalanthus sect. Diphyomene Ruhland (Eriocaulaceae, Poales) and its taxonomic implications - Trovo, Marcelo; Stuetzel, Thomas; Scatena, Vera Lucia [UNESP]; Sano, Paulo Takeo (Elsevier Gmbh, Urban & Fischer Verlag, 2010)
Paepalanthus sect. Diphyomene has inflorescences arranged in umbels. The underlying bauplan seems however to be more complex and composed of several distinct subunits. Despite appearing superficially very similar, the morphology and anatomy of the inflorescences can supply useful information for the understanding of the phylogeny and taxonomy of the group. Inflorescences of Paepalanthus erectifolius, Paepalanthus flaccidus, Paepalanthus giganteus, and Paepalanthus polycladus were analyzed in regard to branching pattern and anatomy. In P. erectifolius, P. giganteus and P. polycladus the structure is a tribotryum, with terminal dibotryum, and with pherophylls bearing lateral dibotrya. In P. flaccidus, the inflorescence is a pleiobotryum, with terminal subunit, and without pherophylls. Secondary inflorescences may occur in all species without regular pattern. Especially when grown in sites without a pronounced seasonality, the distinction between enrichment zone (part of the same inflorescence) and new inflorescences may be obscured. The main anatomical features supplying diagnostic and phylogenetic information are as follows: (a) in the elongated axis, the thickness of the epidermal cell walls and the cortex size; (b) in the bracts, the quantity of parenchyma cells (c) in the scapes, the shape and the presence of a pith tissue. Therefore, P. sect. Diphyomene can be divided in two groups; group A is represented by P. erectifolius, P. giganteus and P. polycladus, and group B is represented by P. flaccidus. The differentiation is based in both, inflorescence structure and anatomy. Group A presents a life cycle and anatomical features similar to species of Actinocephalus. Molecular trees also point that these two groups are closely related. However, inflorescence morphology and blooming sequence are different. Species of group B present an inflorescence structure and anatomical features shared with many genera and species in Eriocaulaceae. The available molecular and morphology based phylogenies still do not allow a precise allocation of the group in the bulk of basal species of Paepalanthus collocated in P. sect. Variabiles. The characters described and used here supply however important information towards this goal. (C) 2009 Elsevier GmbH. All rights reserved.
Keywords: Eriocaulaceae; Inflorescence; Typology; Anatomy; Taxonomy; Phylogeny